West Nile virus, climate change, and circumpolar vulnerability. (15th January 2016) - Hoover, Kara C.; Barker, Christopher M.
Abstract : Climate has strong impacts on the spatial ranges of vector‐borne infectious diseases as well as the timing and intensity of disease outbreaks; these and shifting challenges to human health driven by future climate change are critical concerns. Many diseases of tropical origin, including West Nile virus (WNV), are sensitive to climate and likely to change their distributions in the coming decades. The 1999 outbreak of WNV in North America is an example of rapid viral adaptation to a new geographic area while recent outbreaks in Europe demonstrate the capacity of multiple viral strains to expand rapidly. WNV is one of the most widely distributed arboviruses and has displayed high rates of mutability, adaptability, and virulence. Northward expansion of WNV is happening in Europe and North America and may make WNV an increasingly worrying health risk at higher latitudes. Circumpolar northward expansion of WNV's enzootic range appears unlikely over the coming century—at least for sustained enzootic transmission—but isolated and ephemeral transmission events might occur if the virus were to be introduced by migrating birds during warm months. Human populations in this area are at greater risk for health impacts from WNV transmission due to limited healthcare in rural areas, higher underlying morbidity in indigenous populations, and prolonged human‐environment interactions (in populations engaging in traditional lifestyles). This review presents a multidisciplinary synthesis on WNV and climate change, potential for WNV expansion, and the vulnerability of the circumpolar north. WIREs Clim Change 2016, 7:283–300. doi: 10.1002/wcc.382 This article is categorized under: Assessing Impacts of Climate Change > Evaluating Future Impacts of Climate Change